Progressive collapse behaviour of advanced precast reinforced concrete joints with headed bars and plastic hinge relocation - Nguyen, Van Hung (2023)
This study proposed three types of precast concrete (PC) wet joints, viz., using Headed bars (Type H) to replace hooked bars, placing an Additional bottom bar layer (Type A), or implementing plastic hinge relocation method with X-bent bars (Type X) in the beam-joint region. These detailing features could compensate for negative effects caused by geometric discontinuity at the joint interface and prevent pull-out failure, as observed in conventional PC joints with hooked bars. An experimental investigation based on four interior joints showed that based on the steel content in Type H joint, by increasing respective steel contents of 7% and 8% in Type A and Type X joints, structural resistance to collapse could be enhanced by 34% and 47%, respectively. A fourth specimen of Type A joint incorporated the slab. It was found that although the slab could slightly enhance flexural resistance, it also reduced the joint rotational capacity. Subsequently, component-based joint models (CBM) with a bond-slip model of headed bars were proposed for the three types of PC joints and validated against the test results with satisfactory accuracy. Based on the validated CBMs, parametric studies were conducted for different cases, such as exterior and penultimate joints, under a penultimate column removal scenario. It was found that if the exterior column was too weak, compressive arch action and catenary action could not be effectively triggered, and column failure governed joint behaviour. Hence, to mitigate progressive collapse, the exterior columns and joints must be required to possess a sufficient level of horizontal resistance and stiffness.